Capital formation & foreign investment in underdeveloped areas: an analysis of research needs and program possibilities prepared from a study supported by the Ford Foundation - Wolf, Charles; Sufrin, Sidney C. (Syracuse, N.Y.: Syracuse University Press, 1958)
This study was undertaken to prepare a partial inventory of research already under way or recently completed dealing with capital formation and foreign investment in underdeveloped area; and to use this inventory as a basis for an analysis and evaluation of additional research needs and possibilities for applying, through action programs, the results or ideas derived from recent research in this field.
Bibliography: p. 69-124.
rpm 13/09/2017
Loans
Keywords: Saving and investment; Investments, Foreign; Developing countries